(2x^2+9x+10)(x+4)
Hmmm there is a rule you gotta learn to know how to expand... but i can't remember it
Here are my two cents:
$\displaystyle ({\color{red}2x^2}+{\color[rgb]{.5,0,1}9x}+{\color{blue}10})(x+4)={\color{red}2x^ 2}(x+4)+{\color[rgb]{.5,0,1}9x}(x+4)+{\color{blue}10}(x+4)$
$\displaystyle {\color{red}2x^2}(x+4)={\color{red}2x^2}*x+{\color {red}2x^2}*4$
$\displaystyle {\color[rgb]{.5,0,1}9x}(x+4)={\color[rgb]{.5,0,1}9x}*x+{\color[rgb]{.5,0,1}9x}*4$
$\displaystyle {\color{blue}10}(x+4)={\color{blue}10}*x+{\color{b lue}10}*4$
Do you get it ?